Problem 6 of the 1988 International Mathematical Olympiad notoriously asked:

Let $a$ and $b$ be positive integers and $k=\frac{a^2+b^2}{1+ab}$. Show that if $k$ is an integer then $k$ is a perfect square.

The usual way to show this involves a technique called Vieta jumping. See Wikipedia or this MSE post.

I can follow the Vieta jumping proof, but it seems a bit strained to me. You play around with equations that magically work out at the end. I don't see how anyone could have come up with that problem using that proof.

Is there a natural or canonical way to see the answer to the problem, maybe using (abstract) algebra or more powerful tools? In addition, how can someone come up with a problem like this?

  • 10
    $\begingroup$ Don't think I couldn't smell that Numberphile reference from a mile away ;) $\endgroup$ Aug 21, 2016 at 11:27
  • 2
    $\begingroup$ There's a very simple idea at the core of the usual proof: if $k=\frac{a^2+b^2}{ab+1}$ is an integer, think of $b$ as fixed and see if there's a different $a$ that gives the same quotient. Those who have seen descent arguments before might well think of using that idea to derive a contradiction. (Of course, simple ideas can be extremely non-obvious!) $\endgroup$ Aug 22, 2016 at 5:53
  • 2
    $\begingroup$ Possible duplicate of Alternative proof that $(a^2+b^2)/(ab+1)$ is a square when it's an integer $\endgroup$
    – user565069
    May 27, 2018 at 9:20

7 Answers 7


At the heart of these so-called "Vieta-jumping" techniques are certain symmetries (reflections) on conics. These symmetries govern descent in the group of integer points of the conic. If you wish to develop a deeper understanding of these proofs then I highly recommend that you study them from this more general perspective, where you will find much beauty and unification.

The group laws on conics can be viewed essentially as special cases of the group law on elliptic curves (e.g. see Franz Lemmermeyer's "poor man's" papers), which is a helpful perspective to know. See also Sam Northshield's expositions on associativity of the secant method (both linked here).

If memory serves correct, many of these contest problems are closely associated with so-called Richaud-Degert quadratic irrationals, which have short continued fraction expansions (or, equivalently, small fundamental units). Searching on "Richaud Degert" etc should locate pertinent literature (e.g. Lemmermeyer's Higher descent on Pell Conics 1). Many of the classical results are couched in the language of Pell equations, but it is usually not difficult to translate the results into more geometric language.

So, in summary, your query about a "natural or canonical way to see the answer to the problem" is given a beautiful answer when you study the group laws of conics (and closely related results such as the theory of Pell equations). Studying these results will provide much motivation and intuition for generalizations such as group laws on elliptic curves.

See also Aubry's beautiful reflective generation of primitive Pythagorean triples, which is a special case of modern general results of Wall, Vinberg, Scharlau et al. on reflective lattices, i.e. arithmetic groups of isometries generated by reflections in hyperplanes.

  • 1
    $\begingroup$ This is really great! $\endgroup$
    – nonuser
    Apr 6, 2019 at 20:07
  • 1
    $\begingroup$ See also Samuel Hambleton answer here where he refers to exposition in on this topic in his thesis. $\endgroup$ Apr 22, 2021 at 17:20

The idea has been known (at least) since Gauss' Disquisitiones Arithmeticae 200 years ago. "Vieta jumping" is a name used only in competition manuals, the accepted term in mathematics is "reduction theory of quadratic forms". The reduction-theory solution is the canonical solution, and I do not know any solutions using other methods, but some presentations of the method can make it seem artificial.

The reason more competitors did not solve the problem is that in the quaint old days, high school students were not learning heavy machinery before going to the IMO.

Even knowing the theory, it may not be easy to recognize within a few hours that the problem would fall to a straightforward application of the 'rotation' group of the integer points on the conic (showing that any positive integer solution can be moved to a smaller one with $ab=0$) by writing out the equation as $a^2 - kab + b^2=k$ and turning the handle. Stripped of computational details, that is what the solution does.

It was also known since the 1800's that this type of quadratic form has special properties and is easier to analyze.

For degree $(2,2,...,2)$ equations of higher total degree, such as Markov triples (solutions of $x^2+y^2+z^2=3xyz$), the "Vieta" transformation does not have a specific name, but has been the main tool for organizing the solutions since the first papers in the $19$th century where these equations were analyzed.



Earlier i posted this reply which doesn't make use of Vieta jumping and proves $ k = \gcd(a,b)^2 $. The proof below gives a complete solution for the equation.

First note that: $$ \gcd(a,1+ab) = \gcd(b,1+ab) =1 $$So the common prime factors in the sum of $a^2$ and $b^2$ will remain unchanged and indivisible by $ab+1$. That suggests that we should take $\gcd(a,b)$ out like this: $$ k={\gcd(a,b)^2({({a\over{\gcd(a,b)}})^2+({b\over{\gcd(a,b)}})^2})\over{1+ab}} \tag{1} $$ Observe that also: $$ \gcd(\gcd(a,b)^2,1+ab)) = 1 \tag{2}$$ Because no prime factor in $a$ or $b$ can divide $ab+1$.

Therefore: $$ k'={k\over{\gcd(a,b)^2}} = {{({a\over{\gcd(a,b)}})^2+({b\over{\gcd(a,b)}})^2}\over{1+ab}} $$ also must be an integer because $\gcd(a,b)^2$ divides the numerator of $(1)$ while having no prime factors in common with the denominator because of $(2)$. For clarity write: $$ k'= {{{x_{n-1}}^2+{x_{n}}^2}\over{1+g^2{x_{n-1}}{x_{n}}}} \tag{3} $$ with: $$ g=\gcd(a,b) \text{ and } {x_{n-1}}= {a\over{g}} \text{ and } {x_{n}}= {b\over{g}} \text{ and } \gcd({x_{n-1}},{x_{n}}) = 1 $$ all integers of course.

Any prime divisor of $k'$ must divide ${x_{n-1}}^2 +{x_{n}}^2$. Because $ {x_{n-1}} $ and $ {x_{n}} $ are coprime it cannot divide $ {x_{n-1}} $ and $ {x_{n}} $ both, also it can't divide only one of $ {x_{n-1}} $ and $ {x_{n}} $ so it divides neither: $$ \gcd(k',{x_{n-1}})=\gcd(k',{x_{n}}) =\gcd({x_{n-1}},{x_{n}}) =1 $$

If we can prove $k' = 1$ then we are done because that would mean: $$ k = \gcd(a,b)^2 $$
Now the proof of $ k'= 1 $ (with the assumption : $ 0<{x_{n-1}}<{x_{n}}$ )

Write $(3)$ as: $ {x_{n-1}}^2+{x_{n}}^2=k'g^2{x_{n-1}}{x_{n}}+k' $ . Now if we assume $ k' \ge {x_{n-1}}^2 +{x_{n}} $ then: $$ 1={{x_{n-1}}^2+{x_{n}}^2\over{k'g^2{x_{n-1}}{x_{n}}+k'}} \le {{x_{n-1}}^2+{x_{n}}^2\over{g^2{x_{n-1}}^3{x_{n}} + g^2{x_{n-1}}{x_{n}}^2+{x_{n-1}}^2+{x_{n}}}} < 1 \enspace \implies contradiction \\ $$
So: $ 0 \lt k' \lt {x_{n-1}}^2 + {x_{n}} $ .

Or also: $ -{x_{n}} \lt {x_{n-1}}^2 -k' \tag{*}$

From this it follows that ${x_{n-1}}^2 -k' \ge 0 $ :
We know $\enspace {x_{n}} \mid {x_{n-1}}^2 -k' $. And $(*)$ implies that if $ {x_{n-1}}^2 -k' < 0 $ then $ {x_{n-1}}^2 -k' $ would have to be in $ \left\langle -{x_{n}} , 0 \right\rangle $ . In that interval it would not be divisible by $ {x_{n}} $.

So we are left with the following two possibilities:

Case 1: $ {x_{n-1}}^2 -k' =0 $
Now because $ \gcd(k',{x_{n-1}}) = 1 $ we have $ {x_{n-1}} =1 $ and $ k'=1 $.

Case 2: $ {x_{n-1}}^2 -k' \gt 0 $
In this case the requirement $ {x_{n}} \mid {x_{n-1}}^2 -k' $ tells us that there must be an integer $ {x_{n-2}} $ with: $ 0 < {x_{n-2}} < {x_{n-1}} $ and: $ {x_{n-2}}{x_{n}} = {x_{n-1}}^2 -k' $. With $ (3) $ this means: $\enspace {x_{n}}=k'g^2{x_{n-1}} -{x_{n-2}} $. Substituting this again in $ (3) $ gives: $ {x_{n-1}}^2+ {x_{n-2}}^2 = k'g^2{x_{n-1}}{x_{n-2}}+k' $. So we have the same equation back with $ {x_{n}} $ replaced by a smaller term.
From: $\enspace {x_{n}}=k'g^2{x_{n-1}} -{x_{n-2}} \enspace $ it's also evident that $\enspace \gcd(k',{x_{n-2}})=\gcd({x_{n-1}},{x_{n-2}}) =1 \enspace $.

From the above we conclude that we can repeat taking smaller terms using: $\enspace {x_{i}}=k'g^2{x_{i-1}} -{x_{i-2}} \enspace $ until we reach a pair $ 0,{x_{0}} $ for which case $ 1 $ applies. We see that $ {x_{0}}=1 $ and conclude that $ k'=1 $ $ \enspace \square $

We see that the general solution can be generated using the following recursive formula: $$ x_0=1, x_1 = g^2\\ {x_{n}}= g^2{x_{n-1}} -{x_{n-2}} \tag{4}\\ $$

This gives the following form for the $x_n$ : $$ \text{if $n$ is even:}\enspace x_n= { \sum\limits_{i=0}^{{n\over{2}}} {(-1)^{i+{n\over{2}}}{{n\over{2}}+i\choose {n\over{2}}-i}g^{4i}}} \tag{5}\\ \text{if $n$ is odd:}\enspace x_n= \sum\limits_{i=0}^{{n-1\over{2}}} (-1)^{i+{n-1\over{2}}}{1+{n-1\over{2}}+i \choose {n-1\over{2}}-i}g^{4i+2} \\ $$ Proof of this is by induction:
1) $n$ is even:
$g^2x_{n-1} = \sum\limits_{i=0}^{{n-2\over{2}}} (-1)^{i+{n-2\over{2}}}{1+{n-2\over{2}}+i \choose {n-2\over{2}}-i}g^{4i+4} = $ $\sum\limits_{i=1}^{{n\over{2}}} (-1)^{i +{n\over{2}}}{{n\over{2}}+i-1 \choose {n\over{2}}-i}g^{4i} $ $ = \sum\limits_{i=1}^{{n\over{2}}-1} (-1)^{i +{n\over{2}}}{{n\over{2}}+i-1 \choose {n\over{2}}-i}g^{4i} + (-1)^{n}{n-1 \choose 0}g^{2n} $

$-x_{n-2}= { \sum\limits_{i=0}^{{n-2\over{2}}} {-(-1)^{i+{n-2\over{2}}}{{n-2\over{2}}+i\choose {n-2\over{2}}-i}g^{4i}}} = $ ${ \sum\limits_{i=0}^{{n\over{2}}-1} {(-1)^{i+{n\over{2}}}{{n\over{2}}+i-1\choose {n\over{2}}-i-1}g^{4i}}}$ ${= \sum\limits_{i=1}^{{n\over{2}}-1} {(-1)^{i+{n\over{2}}}{{n\over{2}}+i-1\choose {n\over{2}}-i-1}g^{4i}}} + {(-1)^{{n\over{2}}}{{n\over{2}}-1\choose {n\over{2}}-1}g^{0}} $

${x_{n}}= g^2{x_{n-1}} -{x_{n-2}} \implies $ $ {x_{n}}= {(-1)^{{n\over{2}}}{{n\over{2}}-1\choose {n\over{2}}-1}g^{0} + \sum\limits_{i=1}^{{n\over{2}}-1} (-1)^{i +{n\over{2}}} \bigg[ {{n\over{2}}+i-1 \choose {n\over{2}}-i} +{{n\over{2}}+i-1\choose {n\over{2}}-i-1} \bigg] g^{4i} + (-1)^{n}{n-1 \choose 0}g^{2n}} ={ \sum\limits_{i=0}^{{n\over{2}}} {(-1)^{i+{n\over{2}}}{{n\over{2}}+i\choose {n\over{2}}-i}g^{4i}}} $

2) $n$ is odd:
$x_n={ \sum\limits_{i=0}^{{n-1\over{2}}} {(-1)^{i+{n-1\over{2}}}{{n-1\over{2}}+i\choose {n-1\over{2}}-i}g^{4i+2}}} - \sum\limits_{i=0}^{{n-3\over{2}}} (-1)^{i+{n-3\over{2}}}{1+{n-3\over{2}}+i \choose {n-3\over{2}}-i}g^{4i+2}$ $={ \sum\limits_{i=0}^{{n-3\over{2}}} {(-1)^{i+{n-1\over{2}}}\bigg[{{n-1\over{2}}+i\choose {n-1\over{2}}-i} + {{n-1\over{2}}+i \choose {n-1\over{2}}-i-1} \bigg] g^{4i+2}}} + {(-1)^{{n-1} }{{n-1}\choose 0}g^{2n} } = \sum\limits_{i=0}^{{n-1\over{2}}} (-1)^{i+{n-1\over{2}}}{1+{n-1\over{2}}+i \choose {n-1\over{2}}-i}g^{4i+2} $

Some values: $$ n=1:\enspace g^2 \\ n=2:\enspace g^4-1 \\ n=3:\enspace g^6-2g^2 \\ n=4:\enspace g^8-3g^4+1\\ n=5:\enspace g^{10}-4g^6+3g^2 \\ n=6:\enspace g^{12}-5g^8+6g^4 -1 \\ n=7:\enspace g^{14}-6g^{10}+10g^6 -4g^2 \\ n=8:\enspace g^{16}-7g^{12}+15g^8 -10g^4 +1 \\ n=9:\enspace g^{18}-8g^{14}+21g^{10} -20g^{6} +5g^{2} \\ $$

A solution for the original equation with $ a $ and $ b $: $$ \text{if $n$ is even:}\enspace a_n= { \sum\limits_{i=0}^{{n\over{2}}} {(-1)^{i+{n\over{2}}}{{n\over{2}}+i\choose {n\over{2}}-i}g^{4i+1}}} \tag{6}\\ \text{if $n$ is odd:}\enspace a_n= \sum\limits_{i=0}^{{n-1\over{2}}} (-1)^{i+{n-1\over{2}}}{1+{n-1\over{2}}+i \choose {n-1\over{2}}-i}g^{4i+3} \implies \\ {{a_n}^2+{a_{n+1}}^2\over{a_na_{n+1}+1}}=g^2\\ $$

To answer the question: I started out trying to prove the problem in a more logical way by taking out the $ \gcd(a,b) $ first. But found out I couldn't get any futher without using essentially the same arguments as used in Vieta jumping ( the fact that the equation has two integer roots and the sequence has to reach $ 0 $ eventually ).
But it does seem to me to give more insight if you do it this way. Also this gives a more complete answer to the problem. The general and more abstract Vieta jumping approach in Wikipedia gives you only that $ k $ must be square.

Update 12/14/16. Added a bit of Python code to check $(6)$ . With this you can also generate numbers yourself.

import math

N = 100  # fill in number of iterations
G = 25  # fill in gcd(a,b)

def binom(x, y):
    if y == x:
        return 1
    if y == 1:
        return x
    if y > x:
        return 0

    a = math.factorial(x)
    b = math.factorial(y)
    c = math.factorial(x-y)
    return a // (b*c)

def nextterm(a, gv):
    b = 0
    if a % 2 == 0:  # even case
        for n in range(a//2 + 1):
            b += ((-1)**(n + (a // 2)) *
                  binom(a//2 + n, a//2 - n) * gv**(4*n))
    else:  # odd case
        for n in range((a-1)//2 + 1):
            b += ((-1)**(n + (a-1)//2) *
                  binom((a-1)//2 + n+1, (a-1)//2 - n) * gv**(2 + 4*n))
    return b

def quotient(a, b):
    return (a**2 + b**2) // (a*b + 1)

for n in range(1, N+1):
    u = nextterm(n, G)
    v = nextterm(n-1, G)
    g = G
    j = (((math.sqrt(g**4 - 4) + g**2) / 2)**n *
         (g / (math.sqrt(g**4 - 4))) -
         (((-1 * (math.sqrt(g**4 - 4))) + g**2) / 2)**n *
         (g / (math.sqrt(g**4 - 4))))

    print("------------- iteration %s -------------" % n)
    print("a_%d = %d" % (n-1, G*v))
    print("a_%d = %d" % (n, G*u))
    print("a*_%d = %d" % (n-1, j))
    print("k = %d" % quotient(G*u, G*v))

12/20/16: One last update to give also a closed-form expression in the style of Binet's formula:
$$ \text {The recursive formula : }\\ x_n=g^2x_{n-1}-x_{n-2}\\ \text {Can be written in matrix form : }\\ \begin{pmatrix} x_{n} \\ x_{n-1} \end{pmatrix} = \begin{pmatrix} g^2 & -1 \\ 1 & 0 \end{pmatrix} \begin{pmatrix} x_{n-1} \\ x_{n-2} \end{pmatrix}\\ \text {Or like this : }\\ \vec{F}_{n}=A\vec{F}_{n-1}\\ \text {Which means after applying matrix $A$ several times from start value : }\\ $$ $$ \implies \vec{F}_{n}=A^n\vec{F}_{0} \tag{7}\\ $$ $$ \text{eigenvalues of $A$ are : } \lambda_1={g^2-\sqrt{g^4-4}\over{2}} \text{ and: } \lambda_2={g^2+\sqrt{g^4-4}\over{2}} \\ \text{eigenvectors of $A$ are : }\vec{\mu}=\begin{pmatrix} \lambda_1 \\ 1 \end{pmatrix} \text{ and: } \vec{\nu}=\begin{pmatrix} \lambda_2 \\ 1 \end{pmatrix} \\ \vec{F}_{0}=\begin{pmatrix} 1 \\ 0 \end{pmatrix} = {1\over{\sqrt{g^4-4}}}\vec{\nu} - {1\over{\sqrt{g^4-4}}} \vec{\mu}\\ \text{With $(7)$ this means : }\\ \vec{F}_{n}={{\bigg({g^2+\sqrt{g^4-4}\over{2}}\bigg)}^n\over{\sqrt{g^4-4}}} \begin{pmatrix} 1 \\ 0 \end{pmatrix} - {{\bigg({g^2-\sqrt{g^4-4}\over{2}} \bigg)}^n\over{\sqrt{g^4-4}}} \begin{pmatrix} 1 \\ 0 \end{pmatrix}\\ \text{We can read off values for $x$ and $a$ as : }\\ $$

$$ x_n={{\bigg({g^2+\sqrt{g^4-4}\over{2}}\bigg)}^n\over{\sqrt{g^4-4}}} - {{\bigg({g^2-\sqrt{g^4-4}\over{2}} \bigg)}^n\over{\sqrt{g^4-4}}} \tag{8}\\ a_n={g{\bigg({g^2+\sqrt{g^4-4}\over{2}}\bigg)}^n\over{\sqrt{g^4-4}}} - {g{\bigg({g^2-\sqrt{g^4-4}\over{2}} \bigg)}^n\over{\sqrt{g^4-4}}} \\ $$

  • $\begingroup$ Even though the answer is currently deleted, editing it still bumps the question. It would therefore be nice if you avoid single-character edits and make the edits in larger instalments. Some MathJax tips: \gcd gives you $\gcd$ in standard function style, \implies or \Rightarrow give you $\implies$ (much better than =>), if you prefer $\Longrightarrow$, that's \Longrightarrow. You get the equation numbers on the right hand side by using \tag{n} in the equation, $$\gcd(x,y) = 1 \tag{4},$$ and text within maths mode via \text{some text}. $\endgroup$ Sep 2, 2016 at 13:40
  • $\begingroup$ And note that undeleting the answer won't bump the thread, so when you're almost done, undeleting it before the final edit would get the answer more views than undeleting when it's already perfect and just hoping somebody will see it. $\endgroup$ Sep 2, 2016 at 13:43
  • $\begingroup$ Thanks Daniel, formatting looks much better this time. $\endgroup$ Sep 18, 2016 at 18:11

The same Wikipedia page quotes Arthur Engel about the history of the problem.

Nobody of the six members of the Australian problem committee could solve it … it was [then] sent to the four most renowned Australian number theorists. They were asked to work on it for six hours. None of them could solve it in this time … the jury finally had the courage to choose it as the last problem of the competition. Eleven students gave perfect solutions.

It is implied that the Australians had tried to solve the problem with more general tools and failed, and that the idea of Viète jumping was created specifically for this problem.

Another reason why Viète jumping is the canonical solution to the problem is that the problems of the IMO usually have only a few solutions, with special prizes given out for particularly ingenious ones, such as to Boreico Iurie for IMO 2005 Q3:

Let $x,y,z\in\Bbb R^+$ such that $xyz\ge1$. Prove that $$\frac{x^5-x^2}{x^5+y^2+z^2}+\frac{y^5-y^2}{y^5+z^2+x^2}+\frac{z^5-z^2}{z^5+x^2+y^2}\ge0.$$

(I got this from a book about the mathematical olympiads in China from 2003 to 2006, which had the IMO problems for completeness.) In particular, the Viète jumping proof is the only one with mathematics simple enough for a competitor to understand.

If you insist on a more "natural" solution, a geometric interpretation of the technique is also on the Wikipedia page, involving lattice points on a hyperbola. Dubuque's answer has more on this, including the possible sources for the problem.

  • $\begingroup$ I suspect that the problems did not arise randomly from "playing around" but, rather, as special cases of general results about group laws on conics (or equivalent results on Pell equations) - see my answer. $\endgroup$ Aug 20, 2016 at 14:34
  • 3
    $\begingroup$ I object to "are meant to have only one reasonable solution". For example, when I refereed problem 3 of the 1989 IMO, there were a few totally different solutions, one (for me quite straight-forward and attempted by many) by counting isosceles triangles in two ways and another of which I only remember that it invoked Cauchy-Schwartz in a surprising (to me) manner. Both ways were tricky enough to count as somewhat intended, both were used so often (though somehow correlated to were the participants came from) that neither deserved a special prize. $\endgroup$ Aug 20, 2016 at 15:14
  • $\begingroup$ @HagenvonEitzen Well I've never been to the IMO, but my school has produced a student (Lim Jeck) who got the only perfect score in the world in 2012. So I do understand how the students regularly find new ways around the problems... $\endgroup$ Aug 20, 2016 at 15:39

I posted my answer in this separate subject (click here) i couldn't respond directly because my reputation was too low. After posting my answer my reputation was high enough to also place my reply here. So for my solution click on the link above.

  • $\begingroup$ It can't be evidence and applicable. The formulas have modified the entry of the equation Pell. mathoverflow.net/questions/250172/… The solution is reduced to the Pell equation, and in this bulky record that is not visible. $\endgroup$
    – individ
    Jan 19, 2017 at 9:24
  • $\begingroup$ @individ I don't understand what you're saying. Does your comment refer to the answer above? $\endgroup$ Jan 19, 2017 at 15:07

There is a generalization of this problem too, that proposed in CRUX, Problem 1420, Shailesh Shirali.

If $a, b, c$ are positive integers such that: $$0 < a^2 + b^2 -abc \le c$$ then $a^2 + b^2 -abc$ is perfect square.


I don't have a strong math background, I think my solution is more suitable for the Math olympiad contest as a young student.

Problem Definition: Let $a$ and $b$ be positive integers such that $ab+1$ divides $a^2+b^2$. Show that $\frac{a^2+b^2}{ab+1}$ is the square of an integer.


Let $ t = \frac{a^2+b^2}{ab+1}$. W.L.O.G we assume $1 \le a \le b$.

If $t=1$, we are done.

If $a=b$, we have $2 b^2 = t (b^2+1) \ge 2 (b^2+1)$, contradiction.

If $a = 1$, we have $1+b^2 = t(b+1)$. As $t \equiv 1 (mod~b)$, we have $t \ge 1+b$, contradiction.

Therefore, the major focus is on $t>1$ and $1 < a < b$.

Since $a^2 \equiv t ~(mod~b)$, we define $k$ such that $a^2 = t + k b$, hence $k$ is an integer and $k < a$.

Note that $ t = \frac{a^2+b^2}{ab+1} < \frac{a}{b} + \frac{b}{a} \le 1 + b/2 \le b $.

If $k<0$, we have $a^2 = t+kb \le t - b \le 0$, contradiction.

If $k=0$, we have $t = a^2$, done.

Hence, the only remaining case is $0<k<a$.

In this case, we claim that $$ t = \frac{k^2+a^2}{k a+1} $$

Substitute $t$, we have $ a^2+b^2 = (a^2 - k b)(ab+1)$, hence

$$ b = (a^2 - k b)a - k = a t - k$$

As a result, $k+b = at$ and $kb = a^2-t$, that is, $k$ and $b$ are the solution of the equation $$ x^2 - at x + (a^2-t) = 0 $$ One solution is $x = b$, the other solution is $x = k$, therefore the claim follows.

Consequently, whenever a feasible pair $(a,b)$ exists, we create another feasible pair $(k,a)$. By replacing $(a,b)$ by $(k,a)$ the pair become smaller as $0<k<a<b$. Because all the other case will result in $t$ is a square number, hence by repeating such replacement, we will finally get into the case where $t$ is a square number.



You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .